KAJIAN EVALUASI KEBIJAKAN PEMERINTAH KOTA BANDUNG DALAM PEMBANGUNAN RUANG TERBUKA HIJAU TAHUN 2015-2018 - Vivaldy Mahardhika Putra; Nunik Retno Herawati (Journal of Politic and Government Studies, 2021)
The development of cities often shifts the existence of public spaces, so that the quantity and quality of open spaces, especially Green Open Space (RTH), is currently experiencing a very significant decline and has resulted in a decrease in the quality of the urban environment which has an impact on various aspects of urban life, including frequent flooding, increased pollution air,and decreased community productivity due to limited space available for social interaction Systematically, city green open space functions to support security, prosperity, improve environmental quality and preserve nature. In general, urban green open space consists of linear movement spaces or corridors and island spaces or oases, an area that does not have green open space can cause inconvenience for humans who live in it. In order to support sustainable urban development, an integrated, humane and environmentally friendly urban spatial planning effort is needed. There are one problem formulations in this research,namely (1) How to evaluate the implementation of green open space (RTH) development out by the Bandung city government in 2015-2018,Meanwhile, the purpose of this study is to for the public to assess the extent of the Bandung city government policy in the development of green open space (RTH), whether it is sufficient or not as a public facility or public space itself, This qualitative research was used. Data collection was carried out by interviewing the people of the city of Bandung with the city government of Bandung, reading journals, reading previous research, and documentation.Based on the research results, there are one research findings, namely (1) the availability of land in the city of Bandung has not reached the target(2) The price of land in Bandung is quite high, (3) The population density is so limited that land is limited (4) Every year, there is a threat of switching the use of Green Open Space in the city of Bandung where it is being built . This conversion of function is one of the consequences of the increasing population. When a city has a good potential for economic improvement, it will have consequences for an increase in population. The provision of housing, offices, markets and other building facilities has reduced the area of green open space. These are some of the challenges that must be considered by the city government of Bandung